Hack the planet. (Economist, 2019)
The article explores the increasing prevalence of hacking around the world. Corporations, banks, government agencies and other organizations have suffered hacks and data breaches, including the central bank of Bangladesh and the U.S. National Security Agency (NSA). The rise of the Internet of things (IoT) has been expected to make things worse as malwares have been affecting connected devices such as smart energy meters and surveillance cameras.